2D multichannel seismic reflection raw data (GI Gun) of RV Petr Kottsov in 1998 to the Agulhas Plateau, seismic reflection profile AWI-98016 - Gabriele Uenzelmann-Neben (PANGAEA, 2025)
Seismic reflection data collected on the Agulhas Plateau during with RV Petr Kottsov in 1998. 2 GI-guns were used a seismic source, the data were recorded with a 2400 m (active length) long analog streamer. The data are demultiplexed and unprocessed. No gain, filter or mute have been applied. The data are in SEGY format. See cruise report or ReadMe file for more information on acquisition parameters.